(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
In today’s interconnected world, the boundaries between work and leisure are increasingly dissolving, giving rise to transformative trends like ‘bleisure’ and digital nomadism. This new era, shaped by the remote work revolution and technological advancements (Sthapit, 2022), is redefining how professionals balance productivity with exploration. ‘Bleisure’ combines the words: ‘business’ and ‘leisure,’ and describes a new form of tourism: a business travel that is associated with leisure activities and which can involve guests of the business traveller (Talã et al., 2011).